2017
DOI: 10.2139/ssrn.3093721
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Impacts of Oil Price Shocks on Government Expenditures: Evidence from Saudi Arabia

Abstract: This paper investigates the effect of oil price shocks on government expenditures on the health and education sectors in Saudi Arabia. Using a quarterly dataset 1990Q1-2017Q2 and employing a non-linear autoregressive distributed lag (NARDL) model, our research shows evidence of a non-linear relationship between oil prices and government expenditures in Saudi Arabia, where a negative oil price shock would have a statistically significant different impact in the long run compared to a positive shock. We build up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Lastly, by investigating the oil price shocks–government expenditures nexus in Saudi Arabia with quarterly data from 1990 to 2017, Abdel‐Latif et al . (2018) used a non‐linear ARDL technique and found the link between the two variables to be asymmetric in nature, whereby the nature of impacts from positive and negative oil price shocks on government expenditures differs from each other in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, by investigating the oil price shocks–government expenditures nexus in Saudi Arabia with quarterly data from 1990 to 2017, Abdel‐Latif et al . (2018) used a non‐linear ARDL technique and found the link between the two variables to be asymmetric in nature, whereby the nature of impacts from positive and negative oil price shocks on government expenditures differs from each other in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One notable feature of all these studies is that they were all conducted on developed (and mostly, oil‐importing) economies. Oil‐exporting developing countries started receiving attention on the subject only recently with results from most of the studies being inconclusive (Eltony and Al‐Awadi, 2001; Olomola and Adejumo, 2006; Berument and Ceylan, 2007; Mehrara, 2008; Farzanega and Markwardt, 2009; Iwayemi and Fowowe, 2011; Emami and Adibpour, 2012; Abdel‐Latif et al, 2018), whereas considering the central role played by the oil sector in a typical oil‐exporting developing economy as the main source of foreign exchange earnings, oil price volatility could foment a major disruption in economic activities in the economies.…”
Section: Introductionmentioning
confidence: 99%
“…The positivity and negativity of oil prices can be seen in the economy of oil-exporting countries (Alsamara et al, 2017;Ghalayini, 2011. Education public spending avenue is highly and negatively governed while another public spending negatively and negligibly governed by the oil prices (Abdel-Latif et al, 2018). This implies that the Saudi Arabian government is much concerned about the spending on PSA especially on education, and moderately on another public spending irrespective of lowering of oil prices.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to get the comparative sensitivity and trend of the OP, GDP, and PSA and consider the under and over-allocation of the funds towards the PSA and identify the alternative sources of income to hedge the economy from the shocks of OP. Abdel-Latif et al (2018) studied OP shocks on health and education and found a curvilinear relationship. The negative deviations in the OP significantly and positively correlated with government spending compared to positive deviations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the causality test explores the bi-directional relations between government expenditure and revenues in Saudi Arabia. Abdel-Latif et al (2018) studied the impact of oil prices on government expenditures in Saudi Arabia and found that oil prices deviations affect health and education, directly.…”
Section: Literature Reviewmentioning
confidence: 99%